Relationship between research activities and individual factors among Japanese nursing researchers during the COVID-19 pandemic - Takeuchi, Ayano; Yokota, Shinichiroh; Tomotaki, Ai; Fukahori, Hiroki; Shimpuku, Yoko; Yoshinaga, Naoki (PLOS ONE, 2022)
Aim To explore the individual factors (such as gender, division of household labor, childcare and elder care) and their impact on research activities in the Japanese nursing research community during the early stage of the COVID-19 pandemic from April to June in 2020. Design Cross-sectional study. Methods An online survey with a self-reported questionnaire was conducted on Japan Academy of Nursing Science members to explore the impacts of individual factors among Japanese nursing researchers from April to June 2020. A multivariate logistic regression model was used for data analysis. Results A total of 1,273 participants (90.7% female, 85.8% university faculty) were included in the analysis. This survey showed that no evidence of a significant gender gap was found in research activities in Japanese nursing researchers during the COVID-19 pandemic. Research activities during the pandemic were associated with time and motivation.